ANALISIS EROSI TEBING DAN KONSERVASI LAHAN BERBASIS KEARIFAN LOKAL DI NAGARI SUNGAI SARIAK (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2018)
Watershed management will rely on biophysical activity such as erosion control, reforestation of critical lands, and institutional dimensions such as incentives and regulations related to the economic field. The social dimension in watershed management is more directed to understanding local socio-cultural conditions and using these conditions as a consideration for planning strategies for effective and efficient high-flow watershed management activities. As one of the existing resources, the river flow needs to get attention, both from the community and from the government. From the management of water resources can be traced to environmental damage, especially on erosion. Environmental damages, whether they are influenced by humans or caused by the natural conditions themselves, can be seen from the symptoms and phenomena of river flow behavior from time to time. The state of the river will be worrying if left constantly. This condition could have an impact on the community such as people's houses, rice fields, roads and community estates will be eroded along the river in Nagari Sungai Sariak. This problem is very necessary to be investigated because if left without any effort from the community and the government will have an impact on environmental damage that resulted in fatal damage to the environment, rice fields and homes surrounding the river will erode. It is hoped that by doing this research will be an input for the community and local government in managing the River.